POSIBILIDADES ARTÍSTICAS DEL PAPEL DE PLANTAS REGIONALES - GUZMÁN, ALICIA M.; ANGER, GRACIELA; ANTUNEZ, NORMA T. E.; BRITES, ALDO E.; BULFFE, RITA; HEDMAN, LAURA E.; IBÁÑEZ, ADRIANA M.; VAUTIER, MAURO N.; LOPEZ, RAQUEL A. (Salão do Conhecimento, 2013)
Resumo